Renal Cell Carcinoma in a Horseshoe Kidney Treated with Laparoscopic Partial Nephrectomy - Shinji Ohtake; Takashi Kawahara; Go Noguchi; Noboru Nakaigawa; Kimio Chiba; Hiroji Uemura; Masahiro Yao; Kazuhide Makiyama (Case Reports in Oncological Medicine)
Introduction. Horseshoe kidney is one of the most common congenital renal fusion anomalies. Due to its poor mobility and abnormal vasculature form, surgeons should pay close attention to all anatomical variations. Case Presentation. An 83-year-old woman was referred to our hospital because of left renal tumor in a horseshoe kidney incidentally found by her previous hospital. We performed laparoscopic partial nephrectomy. The pathological diagnosis was clear cell renal cell carcinoma. G2 INFα V-pT1a with a negative surgical margin. No evidence of recurrence has been noted, and the renal function is well preserved at 28 months after surgery. Conclusion. When performing laparoscopic partial nephrectomy for renal carcinoma, especially a horseshoe kidney, preoperative imaging is crucial for identifying the location of the renal vessels.